After Strange Gods: Religion and Secularism in the Early Twentieth-Century Literary Imagination - Huhtinen, Olli (My University, 2017)
In this study I investigate how English modernists wrote about religion and secularism at the beginning of the 1900s. While studies of the early century have emphasised Weberian, Freudian, and Nietzschean discourses of secularisation, the death of religion, and the disenchantment of the society, in this thesis I argue that the ideas of the modernists on these topics were highly divided. The texts of this period present an exceedingly heterogeneous picture of the place and meaning of religion in the world of the modern. The analysis of my thesis focuses on the essay writing, letters, and non-fiction of several key authors of the time. I investigate the texts of T. S. Eliot, Bertrand Russell, and D. H. Lawrence in relation to religion and the secularisation discourses rising to prominence in the debates of the modernists. In three case studies, I analyse Russell’s idea of dismantling the language of religiosity and his emphasis on the psychological and social function of religion, Eliot’s acute fears of the phenomenon of secularism destroying culture, and D. H. Lawrence’s mysticism drawing from occultism popular in the interwar period. The ‘religious’ discussions of the modernists have often been overlooked in the study of their texts. My study provides a broader view of their relationship with this theme than what has been presented before. In contrast to the canonical view, I argue that religion had a formative place amongst the many cultural battles of the epoch.